The Worldview Of Social Harmony Bulding In The Pluralisme A Phenomenology Study in Balun Village, Turi District, Lamongan Regency - Widayati, Elvi (UNUSA Press, 2019)
This phenomenon is interesting because in the midst of religious differences they can build a peaceful and harmonious socio-cultural life system. While in other areas differences in religion or belief become the legitimacy or trigger of conflicts and violence between groups in society. The impact of religious conflict or violence is the occurrence of inequality, insecurity, especially for minority groups, which in turn will affect national integration and unity. From this phenomenon, it is interesting to study how Balun people can process differences in religion, so they can foster and build a culture of tolerance in society. This study aims to uncover the paradigm, factors and models or forms of tolerance in Balun Village, Turi Subdistrict, Lamongan Regency, using research methods with qualitative approaches to informant units, namely Christian (Hindu) and Muslim (figures) and Balun Village Devices. Data collection methods using the method of observation (observation), in-depth interviews (depth interviews) with the Snowball model and literature review and FGD (Focus Group Discusion). Analysis of data using multidisciplinary science, meaning that depends on the data obtained, if the data obtained by religious data analysis uses religious studies and so on. The results of the study, the first Balun community paradigm in understanding its religious teachings (Islam, Hinduism, Christianity) is a substantive inclusive paradigm. Second, the factors underlying the culture of tolerance in Balun are the factors that are understanding of the religious teachings that are substantive-inclusive, pluralist political policies, tolerant socio-cultural traditions, maintained interfaith traditions of marriage. The tolerance model found in Balun is, first, Plural Village (Device) Structure. Second, Multicultural (Democratic) Family, Third, Ngaturi / Kenduri Multicultural and Fourth, Inclusive Da'wah. Hopefully the toll road model built in Balun Village can be an inspiration and mirror for other Indonesian people who are prone to conflict, so that our hopes of building a united, tolerant, advanced, peaceful and harmonious Indonesia can be realized.